Avaliação da análise de segunda ordem em modelos tridimencionais em estruturas de aço considerando irregularidades de geometria - Ficanha, Ricardo (2014)
Analyze the theoretical model of a steel structure is the starting point for defining the internal forces and displacements of the elements and of the whole system. This global analysis enables verification and sizing of individual elements. You should take into consideration the strength and rigidity of the element and the whole structural system. The design of structural systems for medium and large requires experience and good judgment of trained professionals with knowledge of the criteria and regulatory requirements in addition to the advances developed in specific studies by the scientific society. Increased demand combined with the advantages of using steel for building structures generates the need for new methods and criteria for responsible technicians have the necessary support structure to check to ensure the safety and rational use of steel, because the reduce consumption of steel is economical and environmentally linked with the viability of the project in steel. The present study aims to investigate and present the effects of second-order analysis of irregular steel structures in three-dimensional models. We conducted several investigations, such as: The second order effects in structures by reputable scientific society; The behavior of these models when we performed the analysis of elastic buckling, considering the geometric nonlinearity of the structure analyzed in three-dimensional models; To investigate the influence of second order effects in the internal forces of the elements. The software used and commercially utilized is SAP2000, it presents graphical results presentation and easy understanding. The results show the importance of considering the second-order analysis on steel structures, plus the ability to check the sensitivity of the structure under study the effects of second order by linear elastic buckling analysis of the model. Emphasizes the influence of second order effects in the resistant bending moments and no significant change in axial requests resistant elements gravitational requests